Analisis Manajemen Laba terhadap Nilai Perusahaan yang terdaftar di Bursa Efek Indonesia (Studi Khusus: Perusahaan Dagang Otomotif) - Poppy Indriani; Jaka Darmawan; Siti Nurhawa (Universitas Bandar Lampung (UBL), 2014)
The purpose of this study is to investigate and analyze the effect of earnings management on the value of the automobile trading company listed in Indonesia Stock Exchange (IDX). The number of auto sector companies listed in Indonesia Stock Exchange as many as 12 companies. The analysis technique used is simple linear regression.Variable analysis showed a significant effect of earnings management on the value of companies listed on the Indonesia Stock Exchange (Special Study: Automotive Trade Company). It is expected that managers in conducting earnings management uses judgment in financial reporting and the preparation of financial statements of transactions to change on the economic performance of the organization or to influence the outcome in accordance with the contract depends on the accounting numbers that are reported to be in accordance with generally accepted accounting principles.